Preservation of fecal glucocorticoid metabolites and immunoglobulin A through silica gel drying for field studies in horses. Issue 1 (27th October 2019) - Krueger, Konstanze; Marr, Isabell; Dobler, Andrea; Palme, Rupert
Abstract : Stability of stress hormone metabolites, fecal glucocorticoid metabolites (FGMs), and immunoglobulin A (IgA) was evaluated in horse feces dried in an air tight tube on silica gel, for improving stress analysis with fecal samples collected under field conditions with uncontrollable humidity. IgA showed a significant loss, but FGMs were stable and appeared to be reliably preserved. Abstract: Non-invasive methods enable stress evaluation through measuring fecal glucocorticoid metabolites (FGMs), and immunoglobulin A (IgA) in the feces avoiding stressful blood drawing or stressful restraining of animals in the field. However, FGMs and IgA are mostly analysed in freshly frozen samples, which is difficult when fresh samples cannot be frozen immediately or frozen samples cannot be stored or transported. Good results were also derived from air-dried fecal samples, which are hampered by unstable air humidity in the field. These difficulties may be overcome, when drying of samples could be induced with colorless silica gel (SiO2 ) granules in a secure set-up, such as an air tight tube. We determined the speed of drying 1.5 g of a fresh fecal sample from six horses on air and on silica gel. Furthermore, FGMs and IgA were analysed in differently stored subsamples from 12 horses: in frozen fecal samples, in air- or silica gel-dried samples stored for 1 day and for 7 days, and in wet fecal samples kept in a tube at room temperature for 7 days. FGM levels remained stable in feces dried on air or on silica gel for 7 days, whereas IgA quantities showed a significant loss. Under field conditions, when freezing or transporting the frozen samples is not possible and humidity hampers air drying, drying samples on silica gel in air tight tubes appears to be very helpful and reliable for analysing FGMs.